Susceptibilidade in vitro de isolados de Pythium insidiosum frente a aminoglicosídeos e tigeciclina - Mahl, Deise Luiza (2012)
Pythiosis is a chronic disease that affects humans, other mammals and birds. It is caused by the aquatic oomycete Pythium insidiosum. Pythiosis progresses rapidly and can become life threatening if not treated in the early stages. The absence of ergosterol in the cell wall of this oomycete prevents the treatment of pythiosis with antifungal therapy because most antifungal drugs act by inhibiting the synthesis of ergosterol. Members of the genus Pythium are known to be susceptible to some antimicrobial of the tetracycline, macrolide, aminoglycoside and chloramphenicol classes. This study aimed to evaluate the in vitro susceptibility of isolates of P. insidiosum to the aminoglycosides gentamicin, neomycin, paromomycin and streptomycin and to the minocycline derivative tigecycline. The susceptibility tests were carried out with 24 P. insidiosum isolates using the broth microdilution method in accordance with Clinical and Laboratory Standards Institute (CLSI) document M38-A2. The minimum inhibitory concentration (MIC) values for gentamicin, neomycin, paromomycin and streptomycin ranged from 32 to 64 mg/L, and the minimal fungicidal concentration (MFC) values ranged from 32 to 128 mg/L. Tigecycline had a good inhibitory activity, with values of mic MIC (0.25-2 mg/L) and MFC (1-8 mg/L) values. The observed in vitro susceptibility to tigecycline makes this drug a good option for future in vivo assays investigating options of treatment of pythiosis.